Electron Microscopy of Cells Grown on Polyacrylamide Hydrogels. Issue 8 (9th August 2022) - Helmprobst, Frederik; Hupfer, Anna; Lauth, Matthias; Pagenstecher, Axel
Abstract: The composition of the cell culture environment profoundly affects cultured cells. Standard cell culture equipment such as plastic and glass provide extremely stiff surfaces compared to physiological cell environments (i.e., tissue). A growing body of evidence documents the artificial behavior and morphology of cells cultured on supraphysiologically stiff surfaces, such as glass (elastic modulus ca. 70, 000 MPA) or plastic (e.g., polystyrol ca. 3300 MPA). Therefore, polymer‐based hydrogels are increasingly employed as more physiologically appropriate (<100 kPA) supports for 2D or 3D culture. Since multiple properties that influence the cultured cells may be easily adjusted, hydrogels have become versatile tools for studying cells in a more native in vitro environment. Polyacrylamide‐based hydrogels can be used as culture substrates for a broad variety of adherent cells and are easy to handle in most downstream biological assays, such as immunohistochemistry or molecular biology methods. We faced, however, serious difficulties with processing high stiffness polyacrylamide‐based hydrogels for electron microscopy. To overcome this problem, we developed a simple protocol for embedding and processing cells grown on high stiffness polyacrylamide hydrogels that do not require modifications of routine embedding protocols. © 2022 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol : Embedding of polyacrylamide‐based hydrogels for transmission electron microscopy Alternate Protocol 1 : Procedure for detached hydrogels Alternate Protocol 2 : Procedure for attached hydrogels